SEISMIC BASE ISOLATION AND ENERGY ABSORBING DEVICES - Kubilay Kaptan (European Scientific Journal, ESJ, 2013)
Passive energy dissipation systems are described for the control of structures against earthquake vibrations. Classification of passive energy dissipation systems is given and the discussions of the behavior of individual passive devices and systems are provided.In order to investigate the effects of these systems on the response of structures, a typical model building frame is selected. Passive energy dissipation systems are introduced to the model frame and the results are then compared. Although, the UniformBuilding Code (UBC-97) is taken as a base for all design calculations, a series of formulation is proposed in accordance with the Turkish Earthquake Code.Firstly, in order to meet with the objectives of the study, a theoretical four-story plane frame is selected without any passive energy dissipation system. Secondly, the structure is assumed to be base isolated using high damping laminated rubber pads. Thirdly, the viscoelastic dampers are diagonally installed at each floor level of the frame and the seismic analyses are repeated with and without base isolation. In each scenario, the calculations have been carried out using both the equivalent seismic load method and also the linear time history analyses. Linear time history analyses have been based on two different earthquake records, with T1 = 0.13 sec and T2 = 1.43 sec predominant spectral periods. The N-S component of the earthquake ground motion recorded at the Tofaş automobile factory in Bursa, during the August 17, 1999 Kocaeli Earthquake, is taken as a basis. In each case the maximum ground acceleration has been raised to 0.40g. The results for these two different earthquakes, which represent the hard and soft soil conditions, respectively, have been compared by each other.The base shears, storey drifts, and the bending moments at the top of the columns, are presented in a comparative fashion. For all these four different structural models, the relative merits of viscodampers and base isolation are discussed in detail.